Development and evaluation of a high‐throughput single nucleotide polymorphism multiplex assay for assigning pedigrees in common carp. (1st April 2016) - Xu, Jian; Feng, Jingyan; Peng, Wenzhu; Liu, Xiang; Feng, Jianxin; Xu, Peng
Abstract: Accurate pedigree information is critical when managing animal breeding programmes and ensure the highest rate of genetic gain. The abundance of available genomic data and the development of high‐throughput genotyping platforms have facilitated the use of single nucleotide polymorphisms (SNPs) as the best DNA markers for genomic selection studies. Furthermore, the superior qualities of SNPs compared with those of microsatellite markers allow standardization between laboratories, which is crucial for developing an international set of markers for use in traceability studies. The objective of this study was to develop a high‐throughput SNP array to assign common carp pedigrees accurately. A 48‐SNP array was developed based on the Fluidigm genotyping platform, and a phylogenetic analysis was performed to distinguish different pedigrees. A likelihood‐based approach was used to infer parental pairs, and the pair with the highest LOD score (log of the ratio of the likelihood given parentage to likelihood given non‐parentage) was assigned. The SNP genotypes of the offspring and candidate parents tested were collected, and 94% of the offspring were assigned to the most‐likely parent pair, which was consistent with the actual pedigree records. Using this SNP assay will allow implementation of offspring testing at large commercial farms where improved accuracy of pedigree assignments and genetic evaluations will increase genetic gains in the common carp aquaculture industry.